Advanced computing in industrial mathematics : revised selected papers of the 10th Annual Meeting of the Bulgarian Section of SIAM December 21-22, 2015, Sofia, Bulgaria /: revised selected papers of the 10th Annual Meeting of the Bulgarian Section of SIAM December 21-22, 2015, Sofia, Bulgaria. (2017) - Unknown
No abstract available